2017
DOI: 10.3748/wjg.v23.i28.5167
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-derived CXCL12/SDF-1α promotes CXCL6 secretion and co-operatively enhances metastatic potential through the PI3K/Akt/mTOR pathway in colon cancer

Abstract: AIMTo investigate the underlying mechanism by which CXCL12 and CXCL6 influences the metastatic potential of colon cancer and internal relation of colon cancer and stromal cells.METHODSWestern blotting was used to detect the expression of CXCL12 and CXCL6 in colon cancer cells and stromal cells. The co-operative effects of CXCL12 and CXCL6 on proliferation and invasion of colon cancer cells and human umbilical vein endothelial cells (HUVECs) were determined by enzyme-linked immunosorbent assay, and proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 39 publications
1
37
1
Order By: Relevance
“…With respect to other factors implicated in angiogenesis, we found that both docetaxel and vinorelbine increased AKT1, ERK1, ERK2, CXCL6, NOS3 and CCL2 transcription. CXCL6 stimulates breast cancer development triggering the phosphorylation of ERK1 and ERK2, thus inducing migration and growth of endothelial cells 69 . CCL2 turns human breast epithelial cells into a more aggressive and invasive phenotype 70 .…”
Section: Discussionmentioning
confidence: 99%
“…With respect to other factors implicated in angiogenesis, we found that both docetaxel and vinorelbine increased AKT1, ERK1, ERK2, CXCL6, NOS3 and CCL2 transcription. CXCL6 stimulates breast cancer development triggering the phosphorylation of ERK1 and ERK2, thus inducing migration and growth of endothelial cells 69 . CCL2 turns human breast epithelial cells into a more aggressive and invasive phenotype 70 .…”
Section: Discussionmentioning
confidence: 99%
“…A large number of articles have confirmed that PI3K/AKT/mTOR pathway plays an important role in the tumor, and its targeted inhibition has become a hot topic in drug research. [24][25][26][27][28][29] In endometrial carcinoma, the role of PI3K/AKT/ mTOR pathway has been extensively studied. This pathway is associated with the promotion of tumor properties, poor prognosis, and traditional drug resistance, and targeted inhibition of PI3K/AKT/ mTOR pathway in the treatment of endometrial carcinoma has shown excellent results, in both preclinical and clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of CXCL2 destroyed the proliferation and colony formation in CRC cells [55]. Moreover, CXCL2 remarkably promoted the proliferation and migration of HUVECs [56]. But the qPCR results showed no significant difference in CXCL2 expression between HCT116 and NCM460 cell lines.…”
Section: Discussionmentioning
confidence: 99%